Impact of diet supplementation of enzymes during hot weather conditions on milk production and nutrient utilization in Murrah buffaloes - KUMAR, ANUJ; KUMAR, AMIT; SINGH, D K; ROY, DEBASHIS; SINGH, MANOJ KUMAR; SARKAR, T K; KUMAR, ROHIT; YADAV, VIVEK KUMAR (The Indian Journal of Animal Sciences, 2024)
An experiment was conducted to evaluate the impact of diet supplementation of enzymes during hot weather conditions on milk production and nutrient utilization in Murrah buffaloes. Twenty four Murrah buffaloes were distributed randomly into four equal groups (T1, T2, T3 and T4) with six buffaloes in each, on the basis of their body weight, lactation length and test day milk yield. Feeding trial was planned into four treatment groups, viz. T1 (Basal diet without enzyme supplementation), T2 (Basal diet with supplementation of Xylanase @800000 IU), T3 (Basal diet with supplementation of Cellulase @240000 IU) and T4 (Basal diet with supplementation of Xylanase @800000 IU and Cellulase@240000 IU). The results revealed that the average milk yield (5.93 L/day) was higher in T4 as compared to other treatment groups, i.e. 5.47, 5.59 and 5.88 L/day in T1, T2 and T3 group, respectively. Statistically the difference in milk yield was significantly higher in cellulase supplemented groups. The milk fat (%) was significantly higher in enzyme supplemented over control group. The results were shown an increment in all other major milk constituents in enzyme supplemented group in comparison to control group, while statistically the difference was found non-significant. The average DM intake (kg/d, kg/100 kg body wt. and g/kg W0.75) remained static in all treatment groups while the CP intake (g/d, g/100 kg BW and g/kg W0.75) was significantly higher in cellulase supplemented buffaloes. The TDN intake (kg/d, kg/100kg BW and g/kg W0.75) was significantly higher in enzyme supplemented groups. Similarly the digestibility coefficient of CF, NDF and ADF were higher in buffaloes of T3 and T4 over control (T1) group. So, it is concluded from the present study that the milk production and milk composition improves in the combine use of xylanase and cellulase enzyme supplemented groups of buffaloes due to enhanced protein and energy intake and fibre digestibility.